2016
DOI: 10.1002/mc.22484
|View full text |Cite
|
Sign up to set email alerts
|

Mango polyphenolics reduce inflammation in intestinal colitis-involvement of the miR-126/PI3K/AKT/mTOR axis in vitro and in vivo

Abstract: This study sought to elucidate the mechanisms underlying the anti-inflammatory effect of mango (Mangifera Indica L.) polyphenolics containing gallic acid and gallotanins, and the role of the miR-126/PI3K/AKT/mTOR signaling axis in vitro and in vivo. Polyphenolics extracted from mango (var. Keitt) were investigated in lipopolysaccharide (LPS)-treated CCD-18Co cells. Rats received either a beverage with mango polyphenolics or a control beverage, and were exposed to three cycles of 3% dextran sodium sulfate (DSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 52 publications
2
52
0
1
Order By: Relevance
“…Study has showed that mango (Mangifera Indica L.) extract (10 mg GAE/L) treatment is against DSSinduced colonic inflammation and decrease NF-κB and iNOS mRNA levels, as well as NF-κB and p-NF-κB protein levels in rats. In addition, mango polyphenolics treatment attenuates the levels of inflammatory markers via suppression of the PI3K/AKT/mTOR signaling pathway, in part through up-regulation of miRNA-126 in DSS-induced colonic inflammation [125].…”
Section: Tonifying Medicinementioning
confidence: 99%
“…Study has showed that mango (Mangifera Indica L.) extract (10 mg GAE/L) treatment is against DSSinduced colonic inflammation and decrease NF-κB and iNOS mRNA levels, as well as NF-κB and p-NF-κB protein levels in rats. In addition, mango polyphenolics treatment attenuates the levels of inflammatory markers via suppression of the PI3K/AKT/mTOR signaling pathway, in part through up-regulation of miRNA-126 in DSS-induced colonic inflammation [125].…”
Section: Tonifying Medicinementioning
confidence: 99%
“…Caloric intake was calculated on the basis of 3 kcal/g of pellet and 0.612 kcal/mL of juice. a) Reproduced with slight modification from [31]. * The values are statistically significant compared to the control at p < 0.05.…”
Section: Animal Treatment and Tissue Samplingmentioning
confidence: 99%
“…Mango beverage reduced the inflammation score by Values are the mean ± SEM (n = 10 per group). a) Reproduced with slight modification from [31]. * The values are statistically significant compared to the control at p < 0.05.…”
Section: Mango and Pomegranate Beverages Reduced The Inflammatory Resmentioning
confidence: 99%
“…Mango is rich in gallotannins of different degrees of polymerization, gallic acid, and glucosides . Polyphenols from mango extracts exert anti‐cancer, anti‐inflammatory, and anti‐obesogenic effects in vitro and in animal models . In a human clinical trial, obese individuals that consumed freeze‐dried mango pulp for 12 weeks exhibited improved fasting blood glucose levels, suggesting potential health benefits for individuals with metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%